Topical corticosteroids in clinical practice - Devaraj, Navin Kumar; Abdul Rashid, Aneesa; Abdul Manap, Abdul Hadi; Nasir, Shaaira (Malaysian Medical Association, 2019)
Topical corticosteroids are common medications prescribed for skin problems encountered in the primary care or dermatology clinic settings. As skin conditions comprise of around 20% of cases seen in primary care, this article written to guide readers, especially non-dermatologists on the appropriate potency of topical corticosteroids to be chosen for skin problems of patients and to list the side effects both local and systemic.